Synchronisation of Price Cycles in European Housing Markets - Żelazowski, Konrad (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The housing market plays a crucial role in every economy. Its importance is determined not only by the size of the housing sector but also by the number of socio‑economic functions of residential properties. Just as any other market or economy in general, the housing sector develops cyclically. Housing cycles were traditionally considered to be driven by domestic factors. However Economic integration among the countries of the European Union has fostered a general tendency towards synchronisation of national housing cycles. The aim of the research was to identify the properties of housing cycles in selected European countries as well as to verify the degree of their synchronisation. The study covered residential markets in Belgium, France, Holland, Germany, Great Britain, and Italy in the years 1971–2014. The Christiano‑Fitzgerald filter was used to isolate price cycles, while correlation coefficients and the concordance index were used to assess synchronisation. The obtained results confirmed the occurrence of the phenomenon of synchronisation of housing cycles. Its intensity increased at the end of the 1990s, and one of the main causes for this increase was the introduction of a single European currency and the accompanying convergence of financial markets.